Three dimensional modeling analysis of craniofacial hard tissue using various 3D modeling software - Zakaria, Zakiah; Setan, Halim; Majid, Zulkepli (2006)
The aim of the research is to determine the most accurate, reliable and low cost 3D modeling software for 3D modeling of craniofacial hard tissue data (skull). The software namely RapidForm2004, 3D Doctor and 3D Slicer were used to generate the 3D model of the skull from Computed Tomography (CT) scan raw data. The similar CT scan dataset was also process using high quality MIMICS software, where the 3D model of the skull was selected to be a gold standard. The accuracy analysis involved with the deviation analysis between the 3D model generated by the test software and the gold standard. For reliability analysis, the 3D modeling process (in each software) was repeated five times and the RMS value of the deviation with the gold standard was calculated.